ROBERT GILPIN IN REALIST PARADIGM OF INTERNATIONAL RELATIONS DISCIPLINE: RESEARCH PROGRAM, STATE AND INTERNATIONAL SYSTEM. - Ercan Su, Ali (EUL Journal of Social Sciences / LAÜ Sosyal Bilimler Dergisi)
The international relations discipline has been continuously progressing especially since the beginning of 1980s. On the basis of these developments in the discipline, concepts such as state and international system continue to be the major issues of research and debates. After 1980s, research programme also play the major role in debates of the discipline. The aim of the article is to discuss the views of realist academicians particularly views of Gilpin on research programme, state and international system and is to assert that real purpose of the realist scholars in international relations discipline is to produce policies for the USA. In this regard, the views of Robert Gilpin, on research programme, state and international system are discussed in this article. It is seen that Gilpin is well aware in their writings that there are divergent approaches in social sciences in terms of research programmes. Although he accepts the existence of different research programmes on social sciences, he only applies the positivist research program when it comes to scholarship. "The state" is on the other hand has never been elucidated by realist scholars and acknowledged a priori as an entity. Gilpin makes an effort to clarify the state and in some parts, he admits society's influence over the state. However, then, Gilpin approaches state as a solid structure in Waltzian meaning. International system in Gilpin's works, is analysed through "change" concept. He explains that there is a room for change in international system in early 1980s. On the other hand, after the disintegration of the Soviet Bloc, he just indicates that liberal and capitalist bloc triumph over socialism, international system is just capitalist world, with some divisions within it such as the USA, Japan, Germany. The article aims to postulate that even though Gilpin knows the deficiencies of the positivist research programme, he, in the international relations discipline deliberately remains in the realm of the realist paradigm by explicating their views on state and system. Gilpin's basic aim is to find out to the paths for the continuation of American dominance in the sense of realist paradigm. It demonstrates that Robert Cox's argument "theory is always for someone and for some purpose" is valid.